Nanofibrous peptide hydrogel elicits angiogenesis and neurogenesis without drugs, proteins, or cells. (April 2018) - Moore, Amanda N.; Lopez Silva, Tania L.; Carrejo, Nicole C.; Origel Marmolejo, Carlos A.; Li, I-Che; Hartgerink, Jeffrey D.
Abstract: The design of materials for regenerative medicine has focused on delivery of small molecule drugs, proteins, and cells to help accelerate healing. Additionally, biomaterials have been designed with covalently attached mimics of growth factors, cytokines, or key extracellular matrix components allowing the biomaterial itself to drive biological response. While the approach may vary, the goal of biomaterial design has often centered on promoting either cellular infiltration, degradation, vascularization, or innervation of the scaffold. Numerous successful studies have utilized this complex, multicomponent approach; however, we demonstrate here that a simple nanofibrous peptide hydrogel unexpectedly and innately promotes all of these regenerative responses when subcutaneously implanted into the dorsal tissue of healthy rats. Despite containing no small molecule drugs, cells, proteins or protein mimics, the innate response to this material results in rapid cellular infiltration, production of a wide range of cytokines and growth factors by the infiltrating cells, and remodeling of the synthetic material to a natural collagen-containing ECM. During the remodeling process, a strong angiogenic response and an unprecedented degree of innervation is observed. Collectively, this simple peptide-based material provides an ideal foundational system for a variety of bioregenerative approaches.